TPACK Development in Preservice Teacher Education: How Course Design and Self-Efficacy Beliefs Shape Technology Integration - Muhammad Nasheh Ulwan (Barkah Publishing, 2026)
Preservice programs still struggle to prepare teachers who can integrate technology into subject-matter instruction with any real sophistication. TPACK provides a useful lens for understanding why this happens, yet we know surprisingly little about how specific course design choices influence TPACK growth, or how self-efficacy interacts with that process over a full semester. We tracked 55 preservice teachers through a 14-week technology integration course built around extended duration, active learning, collaboration, reflection, and disciplinary grounding. Using an adapted Schmidt et al. TPACK survey and the TISE scale at three time points, we found significant gains across every subdomain. The largest shifts occurred in integrated TPACK (d = 1.61), TPK (d = 1.50), and technology integration self-efficacy (d = 1.53). Open-ended responses clustered around four ideas: practical relevance, collaborative inquiry, reflective growth, and disciplinary grounding. Courses that embed technology work inside authentic disciplinary tasks not as an add on produce measurable, practically meaningful change in both knowledge and confidence. We discuss what this means for program structure.